IS THE MULTIPLE MICRONUTRIENTS BETTER TO REDUCE ANEMIA IN PREGNANCY COMPARED TO IRON- FOLATE ACID SUPLEMENTATION? A SYSTEMATIC REVIEW - Beniqna Maharani Besmaya; Runjati Runjati; Ari Suwondo; Siti Nurharisah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Prevalence of anemia continues to increase among pregnant women in Indonesia. The micronutrients that are needed to reduce the anemia is still lacking to be accessed by pregnant women. This study aims to analyze the effectiveness of multiple micronutrients (MMN) compared to the iron-folic acid to reduce the incidence of anemia among pregnant women. Methods: Systematic review was used in this study using the electronic databases Google Scholar, Science Direct, and PubMed. The articles included in this study were published in 2009-2018 and were written in English language. Results: In total, 380 papers were identified and six articles were included in this study. Study found that the MMN and iron-folic acid had the same effect in influencing the anemia status among pregnant women. However, the MMN had a potential to increase the average of body weight, to reduce the incidence of low birth weight (LBW) and preterm birth among pregnant women. Conclusions: The effectiveness of multi micronutrients in pregnant women is as good as iron-folic acid in reducing the anemia during pregnancy. Further studies need to be conducted to see the effects of MMN on pregnant women by considering other factors such as maternal nutritional status, gestational age, and duration of supplementation